Pedestrian facilities engineering and geometric design - Schoon, John G. 1937- (Thomas Telford, 2010)
This text deals with the engineering and numerical design aspects of pedestrian facilities, such as footways, uncontrolled and controlled crossings along roads and at junctions, roundabouts and driveways where pedestrian and vehicular traffic interact.